An evaluation of SAR image compression techniques - Sakarya, FA; Wei, D; Emek, S (I E E E, COMPUTER SOC PRESS, 1997)
Transform coding based an the Karhunen-Loeve Transform (KLT), the Discrete Cosine Transform (DCT), and the Discrete Wavelet Transform (DWT) is well-understood for optical images. Transform coding applied to synthetic aperture radar (SAR) data, however, has not been well-studied. This paper compares the results of compressing SAR images using KLT, DCT, and DWT coders. We compare the compression results based on six performance criteria- mean-squared error, mean absolute error, peak signal-to-noise ratio, energy compaction, transform gain, and compression ratio.
Keywords: Acoustics; Engineering